Comparison of Impact Accelerations During Performance of Common Ballet Maneuvers: A Pilot Study. Issue 2 (June 2023) - Fallon, Caitlin; Yang, Paj; Lown, Misty; Reilly, Michelle; Bednarz, Nicole; Gamoke, Kyle; Morgan, Alexander; Almonroeder, Thomas Gus
Introduction: Ballet landings produce accelerations that are transmitted proximally up the kinetic chain. If overly excessive/repetitive, these "shocks" to the lower body may contribute to overuse injury. The shocks imposed by different ballet maneuvers are largely unknown at this time, making it difficult to appreciate the physical stresses associated with different maneuvers. Therefore, the purpose of this study was to compare the impact accelerations associated with different common ballet maneuvers. Methods: As part of this study, 11 adolescent ballet dancers performed 9 different common ballet maneuvers: (1) glissade, (2) pas de chat, (3) petit jeté, (4) petit assemblé, (5) grand assemblé, (6) grand jeté, (7) saut de chat, (8) changement, and (9) entrechat quatre . An inertial sensor secured to the pelvis was used to record the peak resultant acceleration during landings ("impact acceleration"). A Friedman test was conducted to compare impact accelerations across the maneuvers and Wilcoxon signed-rank tests were conducted as pairwise comparisons. Results: The omnibus test indicated that there were differences in impact accelerations among the maneuvers ( P  < .001). In general, the glissade (2.08 ± 0.47 g ), pes de chat (2.33 ± 0.23 g ), petit jeté (2.42 ± 0.29 g ), and petite assemblé (2.54 ± 0.47 g ) tended to be the lower impact maneuvers; the grand assemblé (2.90 ± 0.41 g ), grand jeté (2.99 ± 0.33 g ), and saut de chat (3.13 ± 0.54 g ) tended to be the more moderate impact maneuvers; and the changement (4.10 ± 0.48 g ) and entrechat quatre (4.32 ± 0.52 g ) tended to be higher impact maneuvers. Conclusion: These findings may provide clinicians and dance instructors with greater insight regarding the physical stresses imposed by different ballet maneuvers.